صورة المدينة في ديوان عبد العزيز المقالح - يسير, خالد عمر (Latakia University Journal - Arts and Humanities Sciences Series, 2013)
يتناول البحث صورة المدينة في ديوان الشاعر عبد العزيز المقالح، ويتتبَّع الأبعاد الموضوعيَّة لها، ويبيِّن أهميَّتها، وتنوعها، وتوظيفها توظيفاً،ارتبط بقضايا اليمن، وبالعروبة، وبقضايا إنسانية عامَّة.ويتناول أيضاً الأبعاد الجمالية لصورة المدينة، ويتتبع لغتها، وموسيقاها، واستفادتها من التراث استفادة متعدِّدة الأبعاد. وحاول البحث أن يحدِّد خصائص صورة المدينة عند الشاعر التي ارتبطت ارتباطاً وثيقاً بقضايا اليمن واليمنيين، والتي جعلتها متميزةً من غيرها عند شعراء عرب آخرين أمثال: البيَّاتي، وعبد الصبور، وحجازي، وغيرهم. وأشار الباحث إلى نجاح الشاعر في إيصال رسالته إلى القارئ، ساعده على ذلك صياغةٌ لغويةٌ بسيطةٌ قريبة التناول، ينطبق عليها مقولة: (السهل الممتنع)، وصدقُ موقف فكري، ينطبق عليه مقولة: (ماينبع من القلب يصبُّ في القلب). The research deals with city image in the divan of the poet Abdul-Aziz Al-mukaleh. It searches for the objective dimensions of the image and shows its importance and variety devoting itself for the image in a way related to general native, national and human issues. It also deals with the aesthetic dimensions of the city image, and investigates its language, music and how it can get benefit of the heritage in a multi-dimensional way. The research has tried to define the features of the city image at Al-mukaleh, which are related tightly to Yemen and its history, and that has made the city image – at Al-mukaleh – more distinguished than that of other Arab poets, like Al-Bayani, Abdul-Sabour, Hijazi and others. The researcher has also referred to the poet’s success in conveying his message to the reader, and what helped him to do that was a clear linguistic form, which we can say about it: “ easy but rather impossible “. And an honesty of an intellectual attitude which is equal to the saying: “what comes from the heart pours in it “.